Sport Development Index Tegal Regency - Irsyada, Roas; Setiawan, Ipang (Universitas Negeri Semarang, 2020)
The purpose of this study was to determine the development of sports in terms of the sport development index in Tegal Regency. In this study, the method used was a survey method with a quantitative descriptive approach in terms of Sport Development Index (SDI). The research instruments used were observation, interviews, questionnaires and tests. The data obtained were then analyzed using SDI analysis. The data obtained were then analyzed using SDI analysis. The research subjects used a sample of 90 people. The SDI score in Tegal Regency is 0.296 and is in the low category. The government must make policies regarding the development and improvement of the quality and quantity of sports facilities and infrastructure and carry out program planning to encourage and develop recreational sports, such as car-free days in the end. Sports activities such as gymnastics, walking or other recreational sports. activities so that people are more interested in sports activities. People must use the open space for sports wisely and have a sense of each other. In addition, he also uses open space exercises with full responsibility and cares for the environment so that he becomes more comfortable when doing sports activities.